2009
DOI: 10.3957/056.039.0102
|View full text |Cite
|
Sign up to set email alerts
|

Home Range Use of Free-Ranging Cheetah on Farm and Conservation Land in Botswana

Abstract: Cheetah (Acinonyx jubatus) movements should be considered when developing management strategies for long-term survival and coexistence with humans. Although work has been done in Namibia, South Africa and Tanzania little data on the home range and territory size of cheetah in Botswana has been published. This study aimed to estimate male and female home range sizes and daily movement on farmland and a game reserve in Botswana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 21 publications
(25 reference statements)
2
27
1
Order By: Relevance
“…Home ranges were generally larger than the average ranch size of 18 km 2 , with the average 95UD for all cheetahs covering approximately 18 properties. The average area of 12% of core utilization in relation to the 95UD in this study comprised similar percentages to those found in other studies in southern Africa: Namibia (average 13.9%; Marker, Dickman, Mills, Jeo & Macdonald, 2007), Botswana (males 11%, females 10%; Houser, Somers & Boast, 2009) and Kruger (average 13%; Broomhall, Mills & du Toit, 2003) (Fig. 4), despite the large variation in home range sizes recorded between the studies.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Home ranges were generally larger than the average ranch size of 18 km 2 , with the average 95UD for all cheetahs covering approximately 18 properties. The average area of 12% of core utilization in relation to the 95UD in this study comprised similar percentages to those found in other studies in southern Africa: Namibia (average 13.9%; Marker, Dickman, Mills, Jeo & Macdonald, 2007), Botswana (males 11%, females 10%; Houser, Somers & Boast, 2009) and Kruger (average 13%; Broomhall, Mills & du Toit, 2003) (Fig. 4), despite the large variation in home range sizes recorded between the studies.…”
Section: Discussionsupporting
confidence: 71%
“…This makes more open areas sought after as hunting habitat for cheetahs. Additionally, cheetahs outside protected areas are affected by human disturbance that could require them to move larger distances to avoid conflict (Houser et al, 2009). It is likely that the large ranges of cheetahs outside protected areas are driven by the search for suitable habitat in an Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The area is classified as hardveld with some sandveld sections and vegetation ranges from bush to open tree savanna (Houser et al 2009a). Wild game includes common duiker (Sylvicapra grimmia), steenbok (Raphicerus campestris) and greater kudu (Tragelaphus strepsiceros), whilst game farms contain a mixture of small and large antelopes.…”
Section: Study Areamentioning
confidence: 99%